Drivers of vaccine mis/disinformation in the media: from personal beliefs to cultural dimensions - Alfred, Ojonimi Godwin; Catalan-Matamoros, Daniel; Elias, Carlos (Frontiers in Communication, 2025)
IntroductionThe unabated spread of vaccine mis/disinformation poses a great challenge to the achievement of the SDG 3 and Universal Health Coverage (UHC) goals. This systematic review synthesizes the drivers of vaccine mis/disinformation in the media and how geography shapes these drivers through the lens of Hofstede’s cultural dimensions theory.MethodsA search was conducted in Scopus, Web of Science, and PubMed for studies between 2011 and 2024, arriving at a final sample of 27 studies. Emerging drivers of vaccine mis/disinformation identified were categorized into four levels- individual, message, platform, and societal levels with the individual-level (personal-related) drivers dominating the spread of vaccine mis/disinformation.ResultsResults reveal that though individual-level drivers such as being right-wing authoritarian, religious, or being an older male drive the spread of vaccine mis/disinformation on the demand side, message-level drivers including emotional framing and introduction of expert cues in messages also significantly drive the spread of vaccine mis/disinformation from the supply side. Further findings revealed that the prevalent cultural dimension in different climes played significant roles in the prevalence of drivers across certain geographies.DiscussionThe high-power distance culture of developed societies such as North America reflected the prevalence of the message-level driver given the mature and robust research and media ecosystem. Conversely, African and Asian societies which are tilted to the collectivism dimensions of Hofstede’s dimensions theory showed a higher propensity for individual-level drivers, given that the social identity in a collectivist society shapes the behaviors of individuals. The study concluded that cultural theories predict the dominance of how vaccine mis/disinformation spreads in different geographies. Further findings revealed an overlapping complementary relationship between drivers. It was thus recommended that future reviews and studies should deeply explore these relationships and how they shape vaccine mis/disinformation discourse across geographies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, CRD42024601978.